Mineral chemistry of barium- and titanium-bearing biotites in calc-alkaline volcanic rocks from the Mezitler area (Bal?kesir-Dursunbey), western Turkey - Yavuz, Fuat; Örgün, Yüksel; Çelik, Nurgül; Karakaya, Muazzez; Gültekin, Ali Haydar; Şaşmaz, Ahmet (My University, 2002)
Barium- and titanium-bearing biotites from Miocene volcanic rocks of Mezitler area, eastern Bal?kesir, western Turkey are studied. The chemical composition of volcanic rocks range from andesite to rhyodacite. The iron-enrichment index of micas (average I.E. = 0.40) is intermediate between annite and phlogopite. The biotite phenocrysts contain up to 1.72 wt.% BaO and 5.90 wt.% TiO2, with the average formulae (K0.807 Na0.131 Ca0.036 Ba0.027) (Mg1.404 Fe2+ 0.800 Fe3+ 0.131 Ti0.303 Al0.056 Mn0.023) (Si2.832 Al1.167) O10 [(OH)1.976 Cl0.024]. The BaO content of electron-microprobe micas is positively correlated with the Al2O3, TiO2, and FeO contents, and with the I.E., and is negatively correlated with the SiO2, K2O, and MgO contents. Ba and Ti-rich micas are generally found in potassic igneous rocks, in subalkaline and alkaline gabbroic rocks and in contact metamorphic rocks, whereas Ba- and Ti-bearing micas in this study occur in calc-alkaline volcanic rocks that hosted manganese-oxide and barite deposits. Most of the phenocrysts analyzed have deficiencies in their octahedral and partly interlayer sites. Deficiencies in the octahedral sites may arise from the Ti-vacancy and partly the Ti-tschermakite substitution. On the other hand, deficiencies in the interlayer-site are due to the replacement of K by Ba. The substitution mechanism in the Mezitler micas is characterized by Ba + 2Ti + 3Al = (K+Na+Ca) + 3(Mg+Fe+Mn) + 3Si, with an excellent correlation coefficient. In terms of aluminum and titanium contents, micas from the Mezitler area lie on a similar trend parallel to that for metasomatic phlogopites from Canary Island xenoliths, which overlap the field for micas from the Ilha da Trindade xenolith, South Atlantic. Biotite compositions from the Mezitler area fall between the quartz-fayalite-magnetite (QFM) and nickel-nickel oxide (NNO) oxygen fugacity buffers. All these show that Mezitler micas with low to moderate Ba- and Ti-contents may be formed from magmas in a subduction-enriched sub-continental lithospheric mantle environment.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Barium; Biotite; Calc-alkaline